Influence of Perspective of Action Observation Training on Residual Limb Control in Naïve Prosthesis Usage. Issue 5 (2nd September 2016) - Lawson, Delisa T.; Cusack, William F.; Lawson, Regan; Hardy, Ashley; Kistenberg, Robert; Wheaton, Lewis A.
ABSTRACT: Prior work in amputees and partial limb immobilization have shown improved neural and behavioral outcomes in using their residual limb with prosthesis when undergoing observation-based training with a prosthesis-using actor compared to an intact limb. It was posited that these improvements are due to an alignment of user with the actor. It may be affected by visual angles that allow emphasis of critical joint actions which may promote behavioral changes. The purpose of this study was to examine how viewing perspective of observation-based training effects prosthesis adaptation in naïve device users. Twenty nonamputated prosthesis users learned how to use an upper extremity prosthetic device while viewing a training video from either a sagittal or coronal perspective. These views were chosen as they place visual emphasis on different aspects of task performance to the device. The authors found that perspective of actions has a significant role in adaptation of the residual limb while using upper limb prostheses. Perspectives that demonstrate elbow adaptations to prosthesis usage may enhance the functional motor outcomes of action observation therapy. This work has potential implications on how prosthetic device operation is conveyed to persons adapting to prostheses through action observation based therapy.